Markers for internal neoplasia in the horse. Issue 1 (10th December 2022) - Drozdzewska, Karolina; Gehlen, Heidrun
Abstract: The diagnosis of internal neoplasia in horses is challenging. Increased production of hormones physiologic for adult animals (e.g., adrenocorticotropin, norepinephrine, and erythropoietin) or typical for the foetal phase (alpha‐fetoprotein, anti‐Müllerian hormone, and parathyroid‐hormone‐related protein) might aid in tumour diagnostics. Thymidine kinase‐1 and alkaline phosphatase are examples of intracellular enzymes, whose activity in the blood may increase in some neoplasia cases. Furthermore, inappropriate production of abnormal monoclonal or autologous antibodies can accompany lymphoma and multiple myeloma. Many of those tumour markers lead to clinical or laboratory changes, called paraneoplastic syndromes, such as hypercalcaemia and erythrocytosis. The interpretation of the results of the tumour marker measurements in horses is complicated due to many factors affecting the markers' concentration or activity (e.g., young age, pregnancy, and inflammation) and other diseases triggering the same changes. Moreover, the presence of paraneoplastic syndromes is inconsistent, which leads to low sensitivity of those substances as tumour markers. In conclusion, screening for neoplasia in horses is not recommended. The measurement of tumour markers should be performed only in risk groups with suspicious clinical or laboratory findings, and the results should be interpreted with caution. It is advisable to add inflammatory markers to the tumour profile or repeat the measurements. Abstract : The measurement of tumour markers in horses should be performed only in risk groups or in patients with suspicious clinical/laboratory findings (paraneoplastic syndromes). The results should be interpreted with caution as many factors (e.g., young age, pregnancy and inflammation) affect their concentration or activity. It is advisable to add inflammatory markers to the tumour profile or repeat the measurements. Abbreviations: ACTH, adrenocorticotropin; AFP, alpha‐fetoprotein; AMH, anti‐Müllerian hormone; EPO, erythropoietin; NE, norepinephrine; PTHrP, parathyroid‐hormone‐related protein.